Composition of Harpacticoida (Crustacea: Copepoda) and effect of rand reclamation activity in seagrass area of Sungai Pulai, Malaysia - Kassim, Zaleha; Nordin, Amira Syahidah; Ismail, Ahmad (2018)
Sungai Pulai is one of the largest areas for riverine mangroves which associated with other important ecosystem, the seagrass bed and mud flat located in the Tebrau Straits of Johor. The nearby areas experience rapid development activities including land reclamation. This study is carried out to investigate the composition of copepods particularly the Harpacticoida group in the seagrass bed continuously exposed to such land activities. Core samples were taken from three stations which consist of vegetation and non-vegetation areas in the evening during lowest tide in October and November 2017. All samples were fixed with 10% buffered formalin added with Rose Bengal stain. Eight families of harpacticoids were identified; Porcellidiidae Sars., Diossaccidae Sars., Longipediidae Sars, Lang., Laophontidae T. Scott., Canuellidae Lang., Tisbidae Stebbing, Lang , Paramesochridae Lang and Harpacticidae Sars. All families could be found in both vegetated and non-vegetated sediment except for Porcellidiidae Sars which was absent in the non-vegetated sediment. All families showed certain similarity in occurrence within the area of the vegetation or the non-vegetated area. Total Organic Matter (TOM) and sediment characteristic correlated significantly with different families particularly with Canuellidae, Porcellidiidae, Longipediidae and Tisbidae. There is a strong indication that reclamation activity alter the environmental condition thus affect the composition of harpacticoid in term of density and taxonomic group.